PENGELOLAAN DANA DESA DALAM PERSPEKTIF PEMERINTAHAN DESA DI KABUPATEN BUOL - Safri, Mohamad (Katalogis, 2017)
The study intends to explore and describe perspektives on the process of: 1) planning and administration of village funds in Buol Regency; 2) reporting and responsibility of village funds in Buol Regency; 3) supervision of village funds in Buol Regency. Method of research is descriptive qualitative with inductive approach to explore the issue in village funds management including the process of planning, administration, reporting, responsibility, and supervision in the perspective of village goverment. The result finds that 1) the process of planning and andministration of village funds have not been reflecting the need of the village, which is seen from its APB; 2) the process of reporting and responsibility have not been following the schedule so it tends to be slow; 3) the process of village funds supervision is still weak and ineffective.